Pengaruh Kesesuaian Kompensasi, Ketaatan Aturan Akuntansi terhadap Kecenderungan Kecurangan Akuntansi: Peran Efektivitas Pengendalian Internal Sebagai Pemediasi - Bambang Jatmiko; Neva Livia Yusuf; Arif Wahyu Nur Kholid (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
The study aims to examine the appropriateness of compensation and the effect of internal control effectiveness as mediating variable in influencing compliance to accounting rules on the accounting fraud tendencies. This is quantitative study which used a questionnaire survey. The subject of this study is Local Government Organizations (LGO) located in Kotabaru, South Borneo. Hypotheses testing was conducted by employing Structural Equation Modelling-Partial Leas Square (SEM-PLS) technique. This study find that the appropriateness of compensation and internal control effectiveness have positive effect on the accounting fraud tendencies of LGOs. In addition, compliance to accounting rules have positive effect on internal control effectiveness but internal control effectiveness cannot mediate the relationship between compliance to accounting rules and the accounting fraud tendencies significantly.